Magellanic penguins are keystone species in Patagonian coastal systems - Entringer Júnior, Hilton; Udrizar Sauthier, Daniel Edgardo; Vantreels, Ralph .E.T.; Armani, Ana Paula; Srbek Araujo, Ana Carolina; D´Agostino, Romina Laura; Blanco, Gabriela Silvina
The ecological importance of penguins on land remains unknown. To address some of these aspects, we investigated a Magellanic penguin (Spheniscus magellanicus) colony at Cabo dos Bahías (~7,000 pairs), central Patagonia, Argentina. We used camera traps (CT), from September/2022 to January/2023, to compare the activity of vertebrates within (CT=8; 18,384h) and outside the colony (CT=10; 14,928h). Additionally, we employed direct observation (135h), monitored penguin carcasses (CT=8; 1,050h), collected arthropods from them, and performed forensic analysis to identify species interacting with penguin carcasses. Species richness [species=22: including aerial predators as brown skua (Catharacta antarctica) and kelp gull (Larus dominicanus)] and activity were higher within the colony (records/h=0.140) than in the surroundings (species=11; records/h=0.068). Even when considering the species common to both sites [mostly herbivores as guanaco (Lama guanicoe), hare (Lepus europaeus) and lesser rhea (Rhea pennata)], the general activity remained higher within the colony (records/h=0.105). Penguins were depredated and/or scavenged by skua (Catharacta antarctica; eggs/carcasses), kelp gull (Larus dominicanus; eggs/chicks/carcasses), armadillo (Chaetophractus villosus; eggs/chicks/carcasses), Geoffroy’s cat (Leopardus geoffroyi; chicks/adults), vulture (Cathartes aura; carcasses), and caracara (Caracara plancus; carcasses). The carcasses were also used by arthropods (families=12) for consumption and/or metamorphosis. Additionally, kelp gull and dolphin gull (Leucophaeus scoresbii) interacted indirectly with penguins by consuming adults’ regurgitates. Magellanic penguins may be a keystone species in coastal Patagonia; as they are an important food resource that influence the spatial use of marine and terrestrial species, benefiting the functioning of the ecosystems where they breed. Fil: Entringer Júnior, Hilton. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro ...